(untitled) (International Journal of Engineering and Computer Science, 2017)
The colour shade of dyed fabric or printed fabric color defect plays a major role in deciding the quality of fabric color. Hence there is a need for inspection of color shade for its quality. Traditionally inspection for quality of color and defect in color shade is carried out either manually in majority of industries or by using spectrophotometer scanning technique. In this paper, the focus is on the inspection of the variations in colour strength and colour shade of single uniform color using various LAB space models on computer generated image samples without any manual help for interpretation. Among the LAB space models tested, the CMC l:c model has proved to be more accurate than CIE76 and CIE94 for measurement of colour shade variation where coloro matrix is used as a performance parameter. Also colour intensity, I measurement using HSI model has been found to agree fairly with lab spectrometer results